2020
DOI: 10.1101/2020.04.01.019513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chitosan primes plant defence mechanisms againstBotrytis cinerea, including expression of Avr9/Cf-9 rapidly-elicited genes

Abstract: Current crop protection strategies against the fungal pathogen Botrytis cinerea rely on a combination of conventional fungicides and host genetic resistance. However, due to pathogen evolution and legislation in the use of fungicides, these strategies are not sufficient to protect plants against this pathogen. Defence elicitors can stimulate plant defence mechanisms through a phenomenon known as priming. Priming results in a faster and/or stronger expression of resistance upon pathogen recognition by the host.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Overall, transcript levels of defense genes tended to increase in root tissues of chitosan-treated samples, but the increases were not significantly different from control. It could be because gene expression processes take place at the early stage once the plant was initially exposed to chitosan and decline over time (Lopez-Moya et al ., 2017; De Vega et al ., 2021) and our analysis was performed after the peak period of transcriptome changes had passed. Despite statistically insignificant differences, chitosan-induced gene expressions of PR protein 1, endochitinase 2 and PR protein R major form-like were likely to be dose dependent since positive linear relationships were observed from the plots between qPCR relative fold changes and chitosan concentrations (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, transcript levels of defense genes tended to increase in root tissues of chitosan-treated samples, but the increases were not significantly different from control. It could be because gene expression processes take place at the early stage once the plant was initially exposed to chitosan and decline over time (Lopez-Moya et al ., 2017; De Vega et al ., 2021) and our analysis was performed after the peak period of transcriptome changes had passed. Despite statistically insignificant differences, chitosan-induced gene expressions of PR protein 1, endochitinase 2 and PR protein R major form-like were likely to be dose dependent since positive linear relationships were observed from the plots between qPCR relative fold changes and chitosan concentrations (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, treating tomato fruits with chitin suspensions enhanced the gene expressions and protein productions of superoxide dismutase, peroxidase, catalase and chitinase enzymes, reducing grey mold disease caused by Botrytis cinerea (Sun et al ., 2018). Priming tomato leaves with chitosan solution stimulated callose deposition on plant cell wall and accumulation of defense hormones, leading to a reduction of leaf lesions caused by the same fungal pathogen (De Vega et al ., 2021). However, most of those discoveries have been made in foliar parts of the plant due to ease of treatment and subsequent sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Priming is known to activate systemic defense responses only when the plant is challenged by a pathogen or is exposed to abiotic stress (Aranega-Bou et al, 2014). Since natural or synthetic chemicals and infection by pathogens can induce priming effects in plants (Aguado et al, 2019;Westman et al, 2019;De Vega et al, 2021), we hypothesize that the greater positive effect observed with the use of Sedaxane alone, and to a greater extent when in combination with Fludioxonil and Metalaxil-M and in the presence of R. solani could be ascribed to a plant response related to priming. While this hypothesis requires further investigation to clarify the possible involved mechanisms, Sedaxane in combination with Fludioxonil and Metalaxyl-M can be agronomically exploited in a dicot species such as oilseed rape to control Rhizoctonia.…”
Section: Leaf Areamentioning
confidence: 99%
“…Sebagai agen biokontrol, kitosan memiliki beberapa keunggulan diantaranya adalah biodegrabilitas, non-toksik, biokompatibilitas, dan memiliki efek fungisidal (Barikani et al, 2014;Maluin et al, 2019). Kitosan memiliki keunggulan lain yang tidak dimiliki oleh agen biokontrol lainnya, yaitu memiliki potensi untuk menginduksi resistensi tanaman (Liu et al, 2019a;De Vega et al, 2021) dan meningkatkan keanekaragaman mikroba di rizhosfer (Park & Chang, 2012).…”
Section: Pendahuluanunclassified